Emotional Verbalization and Identification of Facial Expressions in Teenagers’ Communication - I. S. Ivanova (Образование и наука)
The paper emphasizes the need for studying the subjective effectiveness criteria of interpersonal communication and importance of effective communication for personality development in adolescence. The problemof undeveloped representation of positive emotions in communication process is discussed. Both the identification and verbalization of emotions are regarded by the author as the basic communication skills. The experimental data regarding the longitude and age levels are described, the gender differences in identification and verbalization of emotions considered. The outcomes of experimental study demonstrate that the accuracy of facial emotional expressions of teenage boys and girls changes at different rates. The prospects of defining the age norms for identification and verbalization of emotions are analyzed.